Status of Sex Education at Elementary Schools in Bangladesh: A Comparative Study among Few Schools in Dhaka - BM Sajjad Hossain; Rushni Korishi; Kamruzzaman Molla (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
Education is considered as a backbone of a nation. For sustainable development, education is the first prerequisite. It plays vital role for socioeconomic development of a society. For the last few decades, Government of Bangladesh has tried to ensure maximum number of participant under the light of education. A lot of projects have been initiated for education development of the nation to spade it to reach the mass and root level. The number of participant has been increased a lot, but the problem is that the education system in Bangladesh has been run under different separate streams and mostly is traditional. Nonetheless, the sex education is absent in most of the curriculum, in fact, at all the main streams elementary school levels in Bangladesh but it is considered as a very much essential part of the schooling process in developed nations. This paper had based on primary data collected from several schools under different streams and attempted to have a comparative study among them. Without including sex education at a large scale in the main stream education process of this country, it is impossible to reduce sexual harassment, children abuse, unwanted pregnancy and related difficulties.